ATTITUDEOF UNIVERSITY STUDENTS TOWARDS PREDICTABLECAREER-FAMILY CONFLICT - Pociūtė, Birutė; Krancaitė, Erika (Acta Paedagogica Vilnensia, 2011)
This article presents research that investigates students’ anticipated work/family conflict and the influence of attitude to future career and family plans. The research sample consisted of 202 participants of Lithuanian universities. Methods: 1) questionnaire for demographic data and students future plans; 2) attitude towards career-family conflict scale; 3) Personal Attributes Questionnaire (PAQ); 5) projective method, to reveal students opinion to gender roles in career and family context. Research findings show that there are three main groups of students’ attitudes toward career-family conflict: 1) priority of family role – family oriented; 2) priority to career role – career oriented; 3) priority to adjust career and family roles – agreement oriented. The results of this study demonstrated the gender differences impact on the attitudes to anticipated career-family conflict: women are more family oriented and men are more career oriented. The students’ marriage status and speciality have also a significant impact on the attitudes towards career-family conflict. The research findings show that the attitude to anticipated career-family conflict will touch students future plans: the family orientated students are planning to chose work, which will be „family friendly“ and the career orientated students are paying attention to future work facilities and prestige. The family orientated and agreement oriented students are planning to start a family earlier and to have more children, than those orientated to career.